THE EVALUATION OF BOBBY BOLA DAN PERI BUKU AJAIB 3 FOR LANGUAGE LEARNING - Rika Hendryani (Department of English Language Education, UIN Sunan Ampel Surabaya, 2018)
Video games have received much attention in recent years as a tool for foreign language learning. Number of research has shown the positive impact of video games on language learning learners. This study is aimed to find out the extent to which Bobby Bola & Peri Buku Ajaib 3 meet the 10 principles for designing video games for foreign learning proposed by Purushotma, Thorne, and Wheatley (2009). The findings of this study show that Bobby Bola & Peri Buku Ajaib 3 adhere only to 2 principles, i.e., the principles of “communication and input mechanism should have a playful spirit to them” and “students should be allowed to spend extra time in activities they enjoy and to minimize time in ones they don't”. The result of this study hopefully would be beneficial to the studies of video games for foreign language learning. It is also hoped that it can provide further information for those who wish to evaluate or use video games as a language learning tool.